2018
DOI: 10.1155/2018/2153971
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Pattern of Particle Crushing of Granular Geomaterials during One-Dimensional Compression

Abstract: This paper focuses on the effect of particle crushing on the behavior of granular geomaterials. Series of high-pressure one-dimensional compression tests were carried out on a quartz sand-gravel. A detail investigation was performed primarily on the compression behavior, the evolution of particle-size distribution (PSD), the fractal pattern of the grading curve, and the amount of particle crushing. It was found that both the yielding state and the state at the maximum compressibility are closely associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…erefore, it is important to study the mechanical properties of rockfill materials by quantitatively describing its gradation of rockfill materials which approaches the true properties and status of raw materials. Zhang and Zhang [25] found that the particle yield and compression state were closely related to the particle-size distribution and fractal curve characteristics of particle breakage through a one-dimensional compression test. Besides, the study found that the fractal dimension D could be used to describe the rockfill particle-size distribution.…”
Section: Fractal Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…erefore, it is important to study the mechanical properties of rockfill materials by quantitatively describing its gradation of rockfill materials which approaches the true properties and status of raw materials. Zhang and Zhang [25] found that the particle yield and compression state were closely related to the particle-size distribution and fractal curve characteristics of particle breakage through a one-dimensional compression test. Besides, the study found that the fractal dimension D could be used to describe the rockfill particle-size distribution.…”
Section: Fractal Theorymentioning
confidence: 99%
“…where η c is the stress ratio under the critical state. According to the energy relationship of the critical state given in equation (25), the dilatancy equation based on the potential theory related to material properties could be obtained as follows:…”
Section: Dilatancy Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the trapezoidal method significantly overestimated the vertical stress in comparison with the field measurement [5,8]. In addition, the ballast aggregates subjected to the cycle train loading, resulting in considerable ballast fouling, such as particle degradation, infiltration of fines from surface, subballast and subgrade infiltration, and weathering factors [2,3,[9][10][11][12][13][14][15][16][17][18][19][20][21]. erefore, the properties of ballast (the internal friction angle of ballast (φ B ) and maximum particle size (D max )) and stress distribution in substructure significantly varied with the real situations in practice [22][23][24].…”
Section: Introductionmentioning
confidence: 98%
“…Many experimental studies have already examined the effect of initial void ratio [ 5 ], particle size [ 6 , 7 , 8 ] and angularity [ 9 , 10 , 11 ], relative density [ 12 , 13 ], material composition [ 14 , 15 ], and saturation degree [ 16 , 17 , 18 ] on particle crushing and thus on soils’ behavior [ 19 ]. The studies of the behavior of sand media at low to intermediate levels of stress are plentiful, but are limited for compression tests at high levels of stress (some tens to some hundreds of MPa).…”
Section: Introductionmentioning
confidence: 99%